PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POP-UP BOOK PADA PEMBELAJARAN BAHASA INDONESIA MATERI MEMBACA KELAS II SD - Khansa Putri Salsabila; Belinda Dewi Regina; Abdurrohman Muzakki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of IT-based Pop-Up Book learning media is expected to help students to improve their understanding of knowledge and improve the learning process of students. The purpose of this study is to produce a product, namely IT-based Pop-Up Book learning media in Indonesian language learning for grade II of elementary school. This research method uses the Research and Development (RnD) type of research and uses the ADDIE development model. The results of this study are to determine the validity of the learning media that was validated by experts. The validation of material experts showed a percentage of 80% and the validation of media experts obtained a percentage of 85%. While the results of the student response questionnaire obtained a percentage of 94% and the teacher's response obtained a percentage of 93%. From the results of these percentages, it shows that the IT-based Pop-Up Book learning media is able to attract the attention and interest of students to make it easier for students to understand the material that has been delivered.